Effects of NaCl stress on seed germination and seedling development of Brassica insularis Moris (Brassicaceae). (24th January 2017) - Santo, A.; Mattana, E.; Frigau, L.; Marzo Pastor, A.; Picher Morelló, M. C.; Bacchetta, G.
Abstract: Brassica insularis is a protected plant that grows on both coastal and inland cliffs in the western Mediterranean Basin. The objective of this study was to test if any variability exists in the salt stress response during seed germination and seedling development in this species relative to its provenance habitat. Variability among three populations in the salt stress effects on seed germination and recovery under different temperatures was evaluated. The effect of nebulisation of a salt solution on seedling development was evaluated between populations growing at different distances from the sea. Seeds of B. insularis could germinate at NaCl concentrations up to 200 mm . Seed viability was negatively affected by salt, and recovery ability decreased with increasing temperature or salinity. Inter‐population variability was detected in salt response during the seed germination phase, as well as in seedling salt spray tolerance. The inland population seedlings had drastically decreased survival and life span and failed to survive to the end of the experiment. In contrast, at least 90% of the coastal seedlings survived, even when sprayed at the highest frequency with salt solution. This study allowed investigation of two natural factors, soil salinity and marine aerosols, widely present in the B. insularis habitat, and provided the first insights into ecology of this protected species and its distribution in the Mediterranean. These results might be useful in understanding the actual distributions of other species with the same ecology that experience these same abiotic parameters.